Post-Soviet features of Hungarian administrative sciences - Rixer, Ádám (Mednarodna revija za javno upravo, 2016)
The post-Soviet features of contemporary administrative sciences in Hungary are not just theoretical issues, they have a strong practical importance, as well. Our starting point is that the scientific field which does not have a clear relation to its own near past, may have neither a sound self-concept nor an exact vision of the future. One of the utmost weaknesses of Hungarian administrative sciences is the partial shortage of elaboration of inner processes after 1945 and the lack of systematic collection of scientifically relevant - but never published - documents of that period of time (1945-1990). Everyday tendencies of administrative sciences also offer some examples of post-Soviet features: the lack of the culture of criticism that is observable within the characteristics of sientific journals, and also within the features of professional record and qualification. Moreover, the positivist way of thinking of representatives of administrative law (and other administrative sciences) results in the dominance of commentaries, i.e. the philosophical and future-oriented, strategic scientific approaches to the problems are often secondary, residual. Actually, these effects in Hungary, compared with the situation within those countries that earlier also belonged to the Soviet bloc, do not show real differences as it has been proven by a questionnaire-based research conducted by the author.
Keywords: administrative sciences; Hungary; javna uprava; Madžarska; public administration; transition; tranzicija; upravne vede